Gender represantations and reitification of women in sertanejo universitário music - Kian, Karla de Oliveira; Alves, Alvaro Marcel Palomo (Revista Hipótese, 2016)
From a socio-historical framework, we are interested in scrutinizing the meanings constructed by a Brazilian music style: sertanejo universitário in relation to sexual genders. For this study, we selected three songs, using as a criterion the largest audience from 2012 to 2014 according to the Brazilian copyright collection agency (ECAD). A Qualitative Epistemological method was used. As a result, we identified that the devaluation of women has its roots in the sexual division of labors, in addition the constructed meaning cores were: reificated relations, pleasure and affection.
Keywords: Socio-historical Psychology; Marxism; Gender representation; Sertaneja music